2012
DOI: 10.1371/journal.pone.0039520
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of miR-21 Reverses Epithelial-Mesenchymal Transition and Cancer Stem Cell Phenotype through AKT/ERK1/2 Inactivation by Targeting PTEN

Abstract: BackgroundAccumulating evidence suggested that epithelial-mesenchymal transition (EMT) and cancer stem cell (CSC) characteristics, both of which contribute to tumor invasion and metastasis, are interrelated with miR-21. MiR-21 is one of the important microRNAs associated with tumor progression and metastasis, but the molecular mechanisms underlying EMT and CSC phenotype during miR-21 contributes to migration and invasion of breast cancer cells remain to be elucidated.Methodology/Principal FindingsIn this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
144
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(148 citation statements)
references
References 40 publications
4
144
0
Order By: Relevance
“…Moreover, Sheng et al [26] found that the protein kinase/phosphatase/phosphatidyl-inositol kinase (AKT/PTEN/ PI3K) signaling pathway is intimately linked with many malignant tumors and their progression, drug resistance, immunity, angiogenesis, and metastasis [27,28]. Furthermore, there have been several studies showing that miR-21 has a significant role in regulating the AKT/ PTEN/ PI3K signaling pathway and contributes to the initiation of carcinogenesis, tumor progression, and metastasis [29,30]. Sheng et al [26] reported that the PTEN gene is a direct target gene of miR-21.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Sheng et al [26] found that the protein kinase/phosphatase/phosphatidyl-inositol kinase (AKT/PTEN/ PI3K) signaling pathway is intimately linked with many malignant tumors and their progression, drug resistance, immunity, angiogenesis, and metastasis [27,28]. Furthermore, there have been several studies showing that miR-21 has a significant role in regulating the AKT/ PTEN/ PI3K signaling pathway and contributes to the initiation of carcinogenesis, tumor progression, and metastasis [29,30]. Sheng et al [26] reported that the PTEN gene is a direct target gene of miR-21.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that activation of p70S6 kinase feedback loop inhibits Rictor phosphorylation, resulting in the suppression of Rictor function [83]. As a result, impaired mTORC2 causes a reduction in the phosphorylation of Akt at serine 473, whose phosphorylation is significantly correlated with cancer stemness [84,85]. These studies underline the increased interest in mTORC2 for its implications in tumorigenesis, however [86], they have also stimulated new ideas on the role played by the amino acids, or some of them in particular, on the pathological mechanisms that lead to cancer or to its prevention.…”
Section: Amino Acids Supplementation As a Cancer Fighting Weaponmentioning
confidence: 97%
“…miR-146a mediates KLF8-induced CSC features by inhibiting the expression of the Numb homolog (NUMB), a Notch signaling inhibitor (19). miR-21 was identified to increase the proportion of BCSCs that expressed the CSC surface biomarkers CD44 + CD242 -and ALDH1 + (20). miR-21 induces the BCSC phenotype through the depletion of phosphatase and tensin homolog and the activation of protein kinase B (AKT) and extracellular signal-related kinase 1/2 (20).…”
Section: Mirnas Participate In Bcsc Formationmentioning
confidence: 99%
“…miR-21 was identified to increase the proportion of BCSCs that expressed the CSC surface biomarkers CD44 + CD242 -and ALDH1 + (20). miR-21 induces the BCSC phenotype through the depletion of phosphatase and tensin homolog and the activation of protein kinase B (AKT) and extracellular signal-related kinase 1/2 (20). miRNA-125a-targeted leukemia inhibitory factor receptor changes the activity of transcriptional co-activator with PDZ-binging motif, an effector molecule in the Hippo pathway, through which miRNA-125a increases the percentage of stem cells in MCF7 cells (21).…”
Section: Mirnas Participate In Bcsc Formationmentioning
confidence: 99%